What Drives Female Labour Force Participation? Comparable Micro-level Evidence from Eight Developing and Emerging Economies - Klasen, Stephan; Le, TU THI NGOC; Pieters, Janneke; Santos Silva, Manuel (The Journal of development studies, 2021)
We investigate the micro-level determinants of labour force participation of urban married women in eight low- and middle-income economies: Bolivia, Brazil, India, Indonesia, Jordan, South Africa, Tanzania, and Vietnam. In order to understand what drives changes and differences in participation rates since the early 2000s, we build a unified empirical framework that allows for comparative analyses across time and space. We find that the returns to the characteristics of women and their families differ substantially across countries, and this explains most of the between-country differences in participation rates. Overall, the economic, social, and institutional constraints that shape women's labour force participation remain largely country-specific. Nonetheless, rising education levels and declining fertility consistently increased participation rates, while rising household incomes contributed negatively in relatively poorer countries, suggesting that a substantial share of women work out of economic necessity.